The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of 1995 Workshop on Applications of Signal Processing to Audio and Accoustics
DOI: 10.1109/aspaa.1995.482963
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of interaural time and magnitude cues to dynamic sound localization

Abstract: This paper presents preliminary data from a study examining the relative contribution of interaural time differences (ITDs) and interaural level differences (ILDs) to the lcxalization of virtual sound sources both with and without head motion. The listeners' task was to estimate the apparent direction and distance of virtual sources presented over headphones. Stimuli were synthesized from minimum phase representations of nonindividualized directional transfer functions. During dynamic conditions, listeners wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…As expected, many subjects reported that stimuli were sometimes externalized while moving their heads, then internalized once they stopped moving their heads. It can therefore be hypothesized that the improvement brought by head movements and head tracking would have been even higher compared to previous studies if subjects had been asked to report externalization while moving their heads, as they were in Begault et al (2001), Wenzel (1995) and Brimijoin et al (2013).…”
Section: A Comparisons With Previous Studiesmentioning
confidence: 85%
See 4 more Smart Citations
“…As expected, many subjects reported that stimuli were sometimes externalized while moving their heads, then internalized once they stopped moving their heads. It can therefore be hypothesized that the improvement brought by head movements and head tracking would have been even higher compared to previous studies if subjects had been asked to report externalization while moving their heads, as they were in Begault et al (2001), Wenzel (1995) and Brimijoin et al (2013).…”
Section: A Comparisons With Previous Studiesmentioning
confidence: 85%
“…In contrast to Begault et al (2001) and Wenzel (1995), subjects in the experiment of Brimijoin et al (2013) were not asked to estimate distance after each presentation, but simply to report a binary choice of whether the stimulus emanated from either inside or outside the head.…”
Section: Head Trackingmentioning
confidence: 99%
See 3 more Smart Citations